The Role of Labuhanbatu Language in Constructing Local Identity within the Digital Era - Elsa Aprianti; Nazirotun Nikmah; Dzaki Naufal Aziz; Rahmadsyah Rangkuti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This paper examines how the Labuhanbatu language, a Malay variety spoken in North Sumatra, contributes to shaping and sustaining local identity in the digital age. The study employs a qualitative descriptive approach by analyzing online materials such as folk narratives, community blogs, and digital glossaries that document the Bilah and Panai dialects. Results indicate that unique phonological traits, such as the nasalized articulation of /r/ into [gh], alongside specific lexical choices, set Labuhanbatu speech apart from standard Indonesian. These features act as markers of cultural identity, reinforcing group cohesion and distinguishing local speech practices. The research also highlights the growing presence of Labuhanbatu language in digital media, including educational archives, social platforms, and computational projects, which reflects ongoing efforts to both preserve and adapt the language. Findings suggest that digital environments provide opportunities for safeguarding linguistic heritage while simultaneously introducing changes through standardization and cross-cultural interaction. Consequently, the Labuhanbatu language continues to function as an essential medium of cultural expression and identity construction in an increasingly globalized context.